Application of Power Droop Control in Multi-motor AC Drive System - HU Xian; WEN Yuliang; HU Liang (Kongzhi Yu Xinxi Jishu)
Aiming at the problem of uneven distribution of output torque in multi-motor AC drive system with hard fixed joint, this paper proposed a power droop based torque balance control strategy, which enables the converter to balance the torque of two AC asynchronous motors without signal interconnection. Experimental results show that the proposed method can effectively balance output torques of the two motors, avoiding the single motor damage caused by long-term overload operation under uneven distribution of torque, and solve the problems of signal mutual transmission and redundancy under the traditional master-slave control mode.